ADVANCED SEISMIC PROCESSING AND IMAGING UTILIZING FWI AND TOMOGRAPHY TO IMAGE SHALLOW GAS CLOUDS AND COMPLEX GEOLOGY IN THE SEPAT FIELD, MALAY BASIN - VERBA, ALBI (2024)
This dissertation presents an in-depth study on the application of advanced seismic processing and imaging techniques, specifically Full Waveform Inversion (FWI) and tomography, to effectively image shallow gas clouds and complex geological structures in the Sepat Field, Malay Basin.